Fate of endocrine disruptor compounds in an anaerobic membrane bioreactor (AnMBR) coupled to an activated sludge reactor. Issue 2 (29th November 2017) - Abargues, M. R.; Ferrer, J.; Bouzas, A.; Seco, A.
Abstract : The occurrence and fate of three groups of micropollutants – alkylphenols, pentachlorophenol and hormones – were studied in a pilot plant consisting of an anaerobic membrane bioreactor (AnMBR) coupled to an activated sludge reactor (University of Cape Town configuration – UCT). Abstract : The occurrence and fate of three groups of micropollutants – alkylphenols, pentachlorophenol and hormones – were studied in a pilot plant consisting of an anaerobic membrane bioreactor (AnMBR) coupled to an activated sludge reactor (University of Cape Town configuration – UCT). Under anaerobic conditions, the octylphenol and technical-nonylphenol soluble concentrations increased producing negative degradation ratios ( i.e., −175 and −118%, respectively). However, high 4- n -nonylphenol and bisphenol-A degradation ratios (92 and 59% for 4- n -nonylphenol and bisphenol-A, respectively) as well as complete pentachlorophenol, estrone, 17β-estradiol and 17α-ethinylestradiol removal were observed. Under aerobic conditions (UCT), octylphenol, technical-nonylphenol, 4- n -nonylphenol and bisphenol-A degradation ratios were higher than 84%. The AnMBR thus removes a high proportion of 4- n -nonylphenol, pentachlorophenol, estrone, 17β-estradiol and 17α-ethinylestradiol, but requires a later post-treatment process (such as UCT) to improve bisphenol-A, octylphenol and technical-nonylphenol degradation ratios. The overall AnMBR–UCT degradation ratios were 48% and 70% for octylphenol and technical-nonylphenol, respectively, and higher than 97% for 4- n -nonylphenol and bisphenol-A. The AnMBR produced a higher micropollutant accumulation in the sludge than the UCT: removal by adsorption in the AnMBR process was between 0.5 and 10%, and less than 0.5% in the UCT process. The combination of AnMBR and UCT technologies produces an effluent stream with low concentrations of micropollutants.